Studi In silico : Toksisitas Senyawa Potensial Sebagai Antikanker Turunan N-((4-Fluorofenil) Karbamatiol) Benzamida - Anindi Lupita Nasyanka; Diah Ratnasari; Jannatun Na'imah; Siti Nur Asiyah (STIKES Rumah Sakit Anwar Medika, 2023)
The potential derivative compound N-((4- Fluorophenyl ) Carbamatiol ) Benzamide a has been predicted to have good activity at the sirtuin-1 receptor which plays a role in triggering cancer on the p53 protein . Toxicity plays a very important role in the safety of the drugs used in the development of new drugs. Therefore, this study aims to determine the toxicity prediction of NBFFT derivatives as anticancer drug candidates. The method used is quantitative descriptive analysis based on the results of in silico toxicity predictions using the Read Across method through the ProTox web server system. on NBFFT derivatives in the ChemBL database with comparators of tenovin and hydroxyurea. The results showed that the derivative compound N-((4 -Fluorophenyl ) carbamatiol ) Benzamide a as an anticancer candidate, it is included in category V (possibly dangerous if consumed) which corresponds to tenovin as a comparison. In addition, predictions of hepatotoxic events were found in these derivative compounds through the MMP stress response pathway, p53, and the nuclear cell nucleus receptor (AhR) type signaling pathway.